Chinese senior primary school students’ civic literacy and its affecting factors - Yao, Yao; Cai, Lian-Yu; Oubibi, Mohamed (Frontiers in Psychology, 2022)
Measuring the current situation of civic literacy of senior primary school students and exploring its influencing factors is the basis for improving the effectiveness of civic education at this stage. The research developed the measurement questionnaire through item analysis, exploratory factor analysis, and other methods. It then was distributed nationwide through stratified sampling and cluster sampling, through which 1642 valid questionnaires were finally collected. The study took mean analysis, difference analysis, correlation analysis, and regression analysis. The statistical results eventually showed that senior pupils’ civic literacy in China is comparatively high. Specifically, the performance of the four dimensions of civic literacy is revealed to be: civic affection > civic cognition > civic competence > civic behavior. Further, a significant difference exists in students’ civic literacy by gender, family location, and whether they have been student leaders. The family social economic status (SES) and school education are respectively significant positive, low, and moderate correlated with students’ civic literacy; moreover, both provide a good explanation for students’ civic literacy. Based on these, primary schools should implement educational compensations for cultivating civic literacy for the senior primary school students of low family SES, and civic education should be carried out according to the specific status of senior students’ civic literacy in primary school.